Determinants of internationalization of SMEs in Malacca / Wan Norhanis Hanini Wan Abdull Hamid and Ihsan Shahrizan - Wan Abdull Hamid, Wan Norhanis Hanini; Shahrizan, Ihsan (2014)
The study purpose is to identify the determinants of internationalization of SMEs in Malacca. It is compulsory to know the factors that influence SMEs in Malacca to do international activities. For this study, the researcher chooses three determinants of internationalization which are human capital, technology of firm and size of firm. There are 90 respondents were chosen consist of SMEs in three areas in Malacca which are Melaka Tengah, Alor Gajah and Jasin. The findings of the study show that human capital and size of firm have significant relationship with internationalization of SMEs in Malacca, however it is a weak relationship. One of the variable which is technology of firm show that there is no significant relationship with the internationalization of SMEs in Malacca. Based on the results, the researcher found that the most significant variable that influenced SMEs in Malacca to go abroad is size of firm. The researcher suggests that by giving international training to the owners of the SMEs would increase their skills and knowledge of international activities. Besides that, these SMEs need to have adequate resources to internationalize by increasing the number of employees and capital.